2020
DOI: 10.1017/s1047951119003329
|View full text |Cite
|
Sign up to set email alerts
|

Does obesity affect the short-term outcomes after cardiothoracic surgery in adolescents with congenital heart disease?

Abstract: Background:Obesity is a modifiable, independent risk factor for mortality and morbidity after cardiovascular surgery in adults. Our objective was to evaluate the impact of obesity on short-term outcomes in adolescents undergoing surgery for congenital heart disease (CHD).Methods:This retrospective chart review included patients 10–18 years of age who underwent CHD surgery. Our exclusion criteria were patients with a known genetic syndrome, heart transplantation, and patients with incomplete medical records. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…According to this recently published study, the elevated risk of morbidity and mortality in the CHD population is exacerbated by obesity [ 27 ]. Obesity has been associated with adverse perioperative outcomes [ 48 ] as well as adverse short-term outcomes after cardiothoracic surgery in patients with CHD [ 49 ]. In contrast, another study on ACHD reported that overweight and moderate obesity were associated with reduced mortality rates, especially in symptomatic ACHD patients and those with complex underlying cardiac defects, replicating the so-called “obesity paradox” in the general population [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to this recently published study, the elevated risk of morbidity and mortality in the CHD population is exacerbated by obesity [ 27 ]. Obesity has been associated with adverse perioperative outcomes [ 48 ] as well as adverse short-term outcomes after cardiothoracic surgery in patients with CHD [ 49 ]. In contrast, another study on ACHD reported that overweight and moderate obesity were associated with reduced mortality rates, especially in symptomatic ACHD patients and those with complex underlying cardiac defects, replicating the so-called “obesity paradox” in the general population [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A smaller single-center study similarly retrospectively reviewed the impact of obesity on peri-operative outcomes in 149 patients and found that obesity was an independent predictor of composite adverse outcomes in multivariate analysis. 20 However, the obese patient group within that cohort did not have a significantly increased risk of post-operative arrhythmia. We investigated the relationship of obesity and post-operative arrhythmias in a large single-center cohort of children and young adults with prospective arrhythmia surveillance after CHD surgery (n = 1250 cases) and found that body mass index was independently associated with post-operative arrhythmias.…”
Section: Discussionmentioning
confidence: 81%
“…17,18 However, although obesity has been shown to increase the risk of post-operative arrhythmias in adults undergoing cardiac surgery, [10][11][12] there are limited data regarding the impact of obesity on post-operative arrhythmias after CHD surgery. [19][20] A large multicenter retrospective cohort utilizing the Society of Thoracic Surgeons Congenital Heart Surgery Database examined the effect of obesity as well as underweight status on peri-operative outcomes in over 18,000 patients. With primary outcomes of operative mortality as well as a composite outcome (operative mortality, major adverse event [including atrioventricular block or arrhythmia requiring permanent pacemaker], wound infection, or prolonged length of stay), a higher operative mortality and incidence of major adverse events was seen in obese and underweight patients as compared to normal-weight/overweight patients.…”
Section: Discussionmentioning
confidence: 99%
“… Delgado-Miguel et al [ 6 ], Malik et al [ 7 ], Stey et al [ 8 ], Kao et al [ 20 ], Seeley et al [ 22 ], Blanco et al [ 23 ], Garey et al [ 24 ], Davies et al [ 25 ], Leet et al [ 26 ], Alshehri et al [ 27 ], Chang et al [ 28 ], García et al [ 29 ], Basques et al [ 33 ], Pandian et al [ 34 ], De la Garza Ramos et al [ 35 ]. …”
Section: Reviewmentioning
confidence: 99%